2017
DOI: 10.1111/ele.12773
|View full text |Cite
|
Sign up to set email alerts
|

Species sorting and stoichiometric plasticity control community C:P ratio of first‐order aquatic consumers

Abstract: Ecological stoichiometry has proven to be invaluable for understanding consumer response to changes in resource quality. Although interactions between trophic levels occur at the community level, most studies focus on single consumer species. In contrast to individual species, communities may deal with trophic mismatch not only through elemental plasticity but also through changes in species composition. Here, we show that a community of first-order consumers (e.g. zooplankton) is able to adjust its stoichiome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 66 publications
3
41
0
Order By: Relevance
“…Although intraspecific variation in body stoichiometry is increasingly being recognised as important (Jeyasingh, Cothran, & Tobler, ), several studies of lake zooplankton have found little to no systematic intraspecific variation in these traits with trophic status (e.g. Prater et al., ; Teurlincx et al., ). However, some stoichiometric variation among lakes nonetheless is likely, and more explicitly considering this variation would strengthen our ability to draw inferences on functional variation with hypereutrophication.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although intraspecific variation in body stoichiometry is increasingly being recognised as important (Jeyasingh, Cothran, & Tobler, ), several studies of lake zooplankton have found little to no systematic intraspecific variation in these traits with trophic status (e.g. Prater et al., ; Teurlincx et al., ). However, some stoichiometric variation among lakes nonetheless is likely, and more explicitly considering this variation would strengthen our ability to draw inferences on functional variation with hypereutrophication.…”
Section: Discussionmentioning
confidence: 99%
“…We then used biomass concentration data from zooplankton tows and average published body stoichiometry values for zooplankton taxa to define stoichiometric traits and estimate total nutrient storage by zooplankton communities per litre of lake volume (Hamre, ; Hébert, Beisner, & Maranger, ; Hessen, Jensen, Kyle, & Elser, ). These traits are particularly well‐suited to analyses that require fixed trait values as zooplankton generally exhibit strong stoichiometric homeostasis (Persson et al., ) and intraspecific stoichiometric variation is relatively constrained among lakes (Prater, Wagner, & Frost, ) and experimental manipulations of food quality (Teurlincx et al., ). As the only rotifers for which we could find published body %N and %P data were Brachionus (Hamre, ; Hessen et al., ), we also calculated zooplankton P storage using the entire range of published rotifer values and excluding rotifers entirely to test for the robustness of our conclusions to this uncertainty.…”
Section: Methodsmentioning
confidence: 99%
“…Changes in N:P have been related to substantial changes in species composition of plant communities (Peñuelas et al. ) and changes in P loads to adjusted C:P ratios in zooplankton communities (Teurlincx et al., ).…”
Section: Evidence From Observational Datamentioning
confidence: 99%
“…The species with more favorable elemental compositions gain then importance and/or there is species turnover (Novotny et al 2007, Yu et al 2011, Poxleitner et al 2016, Du 2017. Changes in N:P have been related to substantial changes in species composition of plant communities and changes in P loads to adjusted C:P ratios in zooplankton communities (Teurlincx et al, 2017).…”
Section: Bn Of Communitiesmentioning
confidence: 99%
“…In contrast to autotrophs, animal consumers have long been considered as being very homeostatic (Andersen & Hessen ; Sterner & Elser ; Anderson et al ). However, evidence for considerable plasticity in consumer body stoichiometry has recently accumulated for a wide range of organisms (Small & Pringle ; Prater et al ; Teurlincx et al ), raising the notion that organisms may take different positions along a continuum between strict regulators and strict conformers (Persson et al ; Meunier et al ). Most work on consumer homeostasis assumes that the somatic elemental composition of consumers responds proportionally to changes in the elemental composition of its food source and that the strength of this response is constant across the whole stoichiometric food quality range (Sterner & Elser ; Persson et al ; Hessen et al ).…”
Section: Introductionmentioning
confidence: 99%